# Intercepts of $$$- 2 x^{2} + 6 x - y - 3 = 0$$$

### Your Input

**Find find the x- and y-intercepts of $$$- 2 x^{2} + 6 x - y - 3 = 0$$$.**

### Solution

To find the x-intercepts, substitute $$$y = 0$$$ into the equation and solve the resulting equation $$$- 2 x^{2} + 6 x - 3 = 0$$$ for $$$x$$$ (use the equation solver).

To find the y-intercepts, substitute $$$x = 0$$$ into the equation and solve the resulting equation $$$- y - 3 = 0$$$ for $$$y$$$ (use the equation solver).

### Answer

**x-intercepts: $$$\left(\frac{3}{2} - \frac{\sqrt{3}}{2}, 0\right)\approx \left(0.633974596215561, 0\right)$$$, $$$\left(\frac{\sqrt{3} + 3}{2}, 0\right)\approx \left(2.366025403784439, 0\right)$$$.**

**y-intercept: $$$\left(0, -3\right)$$$.**

**Graph: see the graphing calculator.**